Seizure prophylaxis in patients with subdural hematoma: retrospective analysis (Revista Argentina de Terapia Intensiva, 2023)
Introduction: The role of seizure prophylaxis in patients with isolated subdural hematoma remains uncertain. Objective: To assess the prevalence of pharmacologic prophylaxis with antiepileptic agents in patients with isolated subdural hematoma and its association with epileptic events from diagnosis to 6-month follow-up. Patients and Methods: A retrospective observational study was performed in patients with isolated subdural hematoma admitted to the ICU. The use of antiepileptic prophylaxis at discharge was evaluated and epileptic events during a period of 6 months were recorded. Results: Fifty-five patients discharged from our Service with a diagnosis of subdural hematoma over 5 years were included and analyzed. The most frequent reason for consultation was traumatic brain injury (44%) followed by new focal neurologic deficit and headache (22% each). Acute subdural hematoma was the most frequent subtype (67%), and 84% of patients had a documented recent traumatic brain injury. Eight (15%) patients received an antiepileptic agent for prophylaxis at the time of hospital discharge. During follow-up, one patient (2%) had a seizure event while receiving anti-seizure prophylaxis. Conclusion: Epileptic events following a subdural hematoma are infrequent and the role of anti-seizure prophylaxis remains uncertain.
Keywords: Siezures; subdural hematoma; seizure prophylaxis